The Ultimate Guide to Differentiation : Achieving Excellence for All - Cowley, Sue (Bloomsbury : Bloomsbury Education, 2018)
This book is the ultimate guide to differentiation in early years, schools and further education settings by Sue Cowley, bestselling author of Getting the Buggers to Behave. It offers over 90 practical and time-saving strategies for effective differentiation in every classroom. The Ultimate Guide to Differentiation demonstrates how teachers already differentiate much of the time, in subtle and creative ways. Sue Cowley shows that we need to understand, acknowledge and celebrate the variety of approaches that teachers already use to differentiate, as well as helping them to develop additional strategies. The book takes the reader through the different methods and approaches to differentiation, providing a step-by-step guide to each. It is broken down into five core areas - planning, resources, learners, teaching and assessment - and readers can dip in and out to find strategies as and when they need them. Written in Sue's much loved realistic, honest and practical style, The Ultimate Guide to Differentiation will help teachers, practitioners and support staff to feel confident that they are meeting the needs of every learner.